Epidemiology and Outcomes of Neonatal Hemophagocytic Lymphohistiocytosis - Balakumar, Niveditha; Sendi, Prithvi; Totapally, Balagangadhar R. (Frontiers in Pediatrics, 2022)
Objectives Neonatal hemophagocytic lymphohistiocytosis (HLH) is a rare entity. The objective of the study was to describe the prevalence, clinical characteristics, interventions and outcomes of neonates diagnosed with HLH in the United States. Methods A retrospective analysis of 2009, 2012, and 2016 Kids' Inpatient Database was performed. Neonates discharged/died with a diagnosis of HLH were identified and analyzed. Results Among 11,130,055 discharges, 76 neonates had a diagnosis of HLH. Fifty-two percent (95% CI: 38.6–63.6) were males and 54% (95% CI: 39.7–68.5) were white. Herpes simplex infection was present in 16% (95% CI: 9.2–28.1). 24.4% (95% CI: 14.5–37.9) received chemotherapy, 11.5% (95% CI: 5.2–23.6) IVIG and 3.6% (95% CI: 0.8–14.4) allogenic hemopoietic stem cell transplantation. Organ dysfunction was commonly seen and severe sepsis was documented in 26.6% (95% CI: 16.4–39.9). Median LOS was 16 (IQR 7–54) days. The mortality was 42% (95% CI: 30.8–55). Conclusions HLH is a rare diagnosis and carries a high mortality in neonates. Herpes simplex virus is the most common infection associated with neonatal HLH. HLH should be considered in the differential diagnosis in neonates presenting with multi-organ dysfunction or sepsis.